Genetic Linkage Analysis of DFNB3, DFNB9 and DFNB21 Loci in GJB2 Negative Families with Autosomal Recessive Non-syndromic Hearing Loss - Marjan MASOUDI; Najmeh AHANGARI; Ali Akbar POURSADEGH ZONOUZI; Ahmad POURSADEGH ZONOUZI; Azim NEJATIZADEH (Tehran University of Medical Sciences, 2016)
Background: Autosomal recessive non-syndromic hearing loss (ARNSHL) is the most common hereditary form of deafness, and exhibits a great deal of genetic heterogeneity. So far, more than seventy various DFNB loci have been mapped for ARNSHL by linkage analysis. The contribution of three common DFNB loci including DFNB3, DFNB9, DFNB21 and gap junction beta-2 (GJB2) gene mutations in ARNSHL was investigated in south of Iran for the first time. Methods: In this descriptive study, we investigated sixteen large families with at least two affected individuals. After DNA extraction, GJB2 gene mutations were analyzed using direct sequencing method. Negative samples for GJB2 gene mutations were analyzed for the linkage to DFNB3, DFNB9 and DFNB21 loci by genotyping the corresponding short tandem repeat (STR) markers using polymerase chain reaction (PCR) and polyacrylamide gel electrophoresis (PAGE) methods. Results: GJB2 mutations (283G>A and 29delT) were causes of hearing loss in 12.5% of families with ARNSHL and no evidence of linkage were found for any of DFNB3, DFNB9 and DFNB21 loci. Conclusion: GJB2 mutations are associated with ARNSHL. We failed to find linkage of the DFNB3, DFNB9 and DFNB21 loci among GJB2 negative families. Therefore, further studies on large-scale population and other loci will be needed to find conclusively linkage of DFNB loci and ARNSHL in the future.